A forward to optimization of antivenom therapy: An in vivo study upon the effectiveness of the antivenom against early and delayed nephrotoxicity induced by the venom of the Iranian scorpion Hemiscorpius lepturus in rat. (15th June 2015) - Pipelzadeh, Mohammad Hassan; Jalali, Amir; Dezfulian, Abdul Rahman; Khorasgani, Zahra Nazari; Sarvestani, Somie; Ghalambor, Amir Hossein; Azarpanah, Armita
Abstract: The aim of the present in vivo study was to identify the optimal effective dose, the most favorable time and the route of administration of the available polyvalent scorpion antivenom against the toxic effects induced by Hemiscorpius lepturus ( H. lepturus ) venom in rat. The end point for assessment included measurement of alanin-amino-peptidase (AAP) and N-acetyl-b-d -glucosaminidase (NAG), biochemical urine analysis and histopathological assessment. The results showed that a single subcutaneous 50 μg of the venom produced significant increase in the AAP and NAG enzyme activity, urinary biochemical parameters and induced histopathological structural abnormalities in the renal system. The optimal effective co-administered dose of the antivenom was 0.5 ml, which when administered 1 and 2 h of envenomation by intravenous (IV) and subcutaneous (SC) routes respectively produced significant protection against these toxic effects. Prudently, the significance of these findings need to be assessed in further clinical studies. Highlights: The effectiveness of the antivenom against H. letuturs scorpion venom was assessed. The optimum dose, route and time were identified in rat. Endpoints were included AAP, NAG enzymes, urine analysis and histological assessment. The dose ratio of the antivenom: venom was 10:1. Delay time for IV and SC routes were 1 and 2 h respectively.